2019
DOI: 10.1002/jcsm.12403
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR‐203 derived from metastatic tissues promotes myopenia in colorectal cancer patients

Abstract: Background Sarcopenia frequently occurs in metastatic cancer patients. Emerging evidence has revealed that various secretory products from metastatic tumours can influence host organs and promote sarcopenia in patients with malignancies. Furthermore, the biological functions of microRNAs in cell‐to‐cell communication by incorporating into neighbouring or distal cells, which have been gradually elucidated in various diseases, including sarcopenia, have been elucidated. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…As CC mediators, miRNAs seem to exert their action by favoring cell apoptosis, protein degradation, or causing downregulation of anabolic processes. For instance, circulating miR-203a-3p secreted by metastatic human colorectal cancer contributed to exacerbation of myopenia in pre-operative cancer patients by targeting survivin (BIRC5), a negative regulator of caspase-dependent apoptosis (67). MiR-21-5p and−206, instead, played an important role in the onset of muscle atrophy in mice under distinct muscledebilitating conditions, including CC.…”
Section: Micrornasmentioning
confidence: 99%
“…As CC mediators, miRNAs seem to exert their action by favoring cell apoptosis, protein degradation, or causing downregulation of anabolic processes. For instance, circulating miR-203a-3p secreted by metastatic human colorectal cancer contributed to exacerbation of myopenia in pre-operative cancer patients by targeting survivin (BIRC5), a negative regulator of caspase-dependent apoptosis (67). MiR-21-5p and−206, instead, played an important role in the onset of muscle atrophy in mice under distinct muscledebilitating conditions, including CC.…”
Section: Micrornasmentioning
confidence: 99%
“…Herein, we for the first time illustrated miR-203 as another anti-tumour executor of luteolin. miR-203 has been widely identified as an anti-tumour miRNA [17][18][19][20], but its exact function in breast cancer is confusing. Two of the previous studies reported miR-203 as an oncogene, as silence of its expression inhibited breast cancer cells colony formation, transformation, stemness and migration [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…miR-203 is one of such oncogenic miRNA that locates at chromosome 14q32.33. The antitumour role of miR-203 has been found in various kinds of cancers, such as colorectal cancer [17], hepatocellular carcinoma [18], gastric cancer [19], prostate cancer [20] and so forth. However, miR-203 exerted contradictory roles in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Okugawa et al, demonstrated that circulating miR-21 levels increased in cachectic colorectal cancer patients (Okugawa et al, 2018). Recently they also reported that circulating miR-203 is able to predict myopenia in metastatic colorectal cancer patients (Okugawa et al, 2019).…”
Section: Potential Use Of Circulating Micrornas As Biomarkers For Canmentioning
confidence: 98%